The development of religiosity framework for Muslim employees / Azman Che Omar and Ahmad Mudzfir Zubir - Che Omar, Azman; Zubir, Ahmad Mudzfir (PENERBIT PRESS Universiti Teknologi MARA, 2012)
The purpose of the paper is to critically review the level of religiosity of Muslim employees towards their work performances. The main objective of this exploratory study is to examine the relationship between the religiosity with the work ethics and the work performance. The religiosity of Muslim employees should lead to the attitudes and behaviour that conform to the Islamic teachings. For Muslim, doing the work with Islamic work ethics should be viewed as an amanah obligation to Allah s.w.t. Thus, it becomes a noble effort and those who work hard are more likely to be better rewarded in the future. Conversely, not working hard is seen to cause failure in life. The paper explores the main properties of religiosity that has been investigated in various empirical researches. Its relationship with Islamic work ethics is also discussed. The proposed research methodology is explained at the end of the paper.